PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL PADA PENGUASAAN KONSEP PESERTA DIDIK SD KELAS V - Juni Artha Juneli; Atep Sujana; J. Julia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
The low concept mastery possessed by students influences learning outcomes that are often far from the standard of assessment, especially in natural science learning subjects. The research described in this article is generally aimed to develop digital comic learning media that could build the students' concept mastery. The research used a quantitative approach with quantitative-descriptive methods. The method used was Research and Development (R&D), which is a scientific method to obtain data so that it could be used to produce, develop, and validate products. Digital comic as learning media was first developed through a product validation that involved material and media experts to determine the feasibility and effectiveness of the product. Then, digital comic products were tested to determine the students' concept mastery after participating in learning activities. The participants of the research involved 23 fifth-grade students in one of the public elementary schools in Karimun Riau Islands. The results showed that digital comics were appropriate and effective to be used as learning media that could help teachers in natural science learning subject activities. The learning media of digital comics could also improve the fifth-grade students' concept mastery as evidenced by the improvement of students’ learning outcomes.